"Itching to make an impact": constructing the mobile Singaporean voluntourist in Instagram travel narratives. Issue 3 (27th May 2022) - Pak, Vincent; Hiramoto, Mie
ABSTRACT: This study investigates voluntourism activity directed by a local university in Singapore. The phenomenological experience of participating in voluntourism is captured in the form of reflective Instagram posts where voluntourists often report attaining a sense of personal growth and development, centering their experiences at the expense of their underprivileged counterparts. By conducting a text and visual analysis of their Instagram posts, we venture that the participants' travel narratives evince a collaborative effort between their transnational mobilities and the subsequent post-trip reflections to linguistically construct a global selfhood in relation to the underprivileged subject. Such self-presentations are deemed to be culturally valuable, and very much influenced by and in congruence with the Singapore government's globalization project.